Characterization of the Different Chemical Components and Nutritional Properties of Two Eryngium Species - Mozhgan Roudbari; Mohsen Barzegar; Esther Sendra; Isabel Casanova-Martínez; Marcos Rodríguez-Estrada; Ángel A. Carbonell-Barrachina (Foods, 2025)
This study aimed to investigate the nutritional value and potential for herbal tea production of two species Eryngium. The analysis includes the quantification of lipids, proteins, organic acids (HPLC-MS), sugars (HPLC-MS), phenolic compounds (HPLC-MS-MS), volatile compounds (GC-MS), fatty acids (GC-MS), amino acids (HPLC-MS-MS), some minerals (ICP-MS), total phenolic content, and antioxidant activities of Eryngium billardieri flowers (EBF) and thorns (EBT), as well as Eryngium planum flowers (EPF) and thorns (EPT). The results indicate that EPF and EPT exhibit elevated levels of protein (11.2%) and sugars (224.2 mg/gdw), respectively. Whereas, EBF demonstrates a higher concentration of amino acids (7.13 mg/100 gdw) and total phenolic content (19.25 mg GAE/gdw), which correlates with pronounced antioxidant properties. Oleic acid was notable in E. billardieri, while linoleic and α-linolenic acids were predominant in E. planum. Furthermore, essential minerals such as Fe, Mn, Zn, Mg, K, Ca, and P were also determined. Sensory evaluations by panelists confirmed that tea derived from the studied species possesses favorable taste and flavor profiles, attributed to its rich volatile compounds. These findings highlight the nutritional value of Eryngium species as a functional ingredient in the food industry. Additionally, their antioxidant properties suggest promising uses in pharmaceutical applications.